Luenberger-based State-Of-Charge evaluation and experimental validation with lithium cells. (August 2020) - Ceraolo, M.; Lutzemberger, G.; Poli, D.; Scarpelli, C.
Highlights: Evaluation of State-Of-Charge of lithium cells was performed. A mathematical model has been defined and experimentally validated. Different techniques for determination of model parameters were considered. A Luenberger-style technique for run-time SOC evaluation was used and verified. Long term stability of the technique and effects of sensor accuracy were analysed. Abstract: This paper presents a technique to estimate the State-Of-Charge of lithium cells, based on a Luenberger state estimator. Although this approach is not new, in this paper several practical implementation details are discussed, including techniques to find numerical parameters of the required cell model with tests that give enough precision with limited testing effort. Additionally, the effects of limited sensor precision on the final estimated State-Of-Charge are discussed. The paper also provides guidelines on how to keep the cell model (needed for the estimator to operate satisfactorily) updated during normal operations. The results achieved with the proposed approach show very interesting results, also when compared to other techniques described in the recent literature.